Availability and distribution of safe abortion services in rural areas: a facility assessment study in Madhya Pradesh, India - Sarika Chaturvedi; Sayyed Ali; Bharat Randive; Yogesh Sabde; Vishal Diwan; Ayesha De Costa (Taylor & Francis Group, 2015)
Background: Unsafe abortion contributes to a significant portion of maternal mortality in India. Access to safe abortion care is known to reduce maternal mortality. Availability and distribution of abortion care facilities can influence women's access to these services, especially in rural areas. Objectives: To assess the availability and distribution of abortion care at facilities providing childbirth care in three districts of Madhya Pradesh (MP) province of India. Design: Three socio demographically heterogeneous districts of MP were selected for this study. Facilities conducting at least 10 deliveries a month were surveyed to assess availability and provision of abortion services using UN signal functions for emergency obstetric care. Geographical Information System was used for visualisation of the distribution of facilities. Results: The three districts had 99 facilities that conducted >10 deliveries a month: 74 in public and 25 in private sector. Overall, 48% of facilities reported an ability to provide safe surgical abortion service. Of public centres, 32% reported the ability compared to 100% among private centres while 18% of public centres and 77% of private centres had performed an abortion in the last 3 months. The availability of abortion services was higher at higher facility levels with better equipped and skilled personnel availability, in urban areas and in private sector facilities. Conclusions: Findings showed that availability of safe abortion care is limited especially in rural areas. More emphasis on providing safe abortion services, particularly at primary care level, is important to more significantly dent maternal mortality in India.